THE ANALYSIS OF STUDENT’S ERROR IN COMPLETING THE MATERIAL OF ALGEBRA CLASS VIII - Indah Silastiningsih; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
One indicator of the success of mathematics learning can be seen from the test results of the students. The test results not only to assess the students but through the test results can be known the difficulties faced by students and also the errors that many students do. Furthermore, the error is analyzed in-depth and then determined the appropriate action to be able to reduce the same error. The purpose of this study is to know and describe what kind of mistakes students make and find out the most mistakes that are often made. This research is qualitative descriptive research. The subject of his research is the students of class VIII SMP Negeri 1 Yogyakarta. The research object is the student's mistake in doing questions test on the Linear Equation System of Two Variables. This research's main instruments are the researcher itself, and the aid instrument is five questions test and interview guides. The technique of analysis used is the triangulation technique. The results of this research indicate that students make mistakes that are: 1. the error of concept, that is error determine a mathematical model and how to write an example of the problem; 2. the errors of principle, that is an error in understanding Linear Equation System of Two Variables settlement method; 3. the operation of the error, that is errors due to incorrect calculations.